Exploring The Experiences of Two Informatics Teachers in Using Zoom Interactive Media in Rural Junior High Schools in East Java: A Narrative Study - Muhammad Yudli Ulhaq; Arico Ayani Suparto; Siti Seituni (Journal of Educational Sciences, 2026)
Many academics have researched the use of Zoom interactive media at various levels of education. However, little research has been conducted on the use of Zoom interactive media in rural areas. This study details the use of Zoom in a junior high school located in a rural area in Bondowoso Regency, East Java, along with the various problems encountered. This research uses narrative research with the aim of analyzing the experiences of two informatics teachers in using interactive Zoom media in rural areas. Information was obtained through narrative stories/interviews conducted repeatedly and direct observation to maintain data validity. These results suggest that narrative research has three dimensions: looking back (reasons and motivations of participants), looking inward (implementation of Zoom interactive media), looking forward (goals and expectations in using Zoom in Informatics Education). The study's conclusion is that the primary elements influencing the usage of interactive Zoom media in the classroom are a teacher's proficiency, educational background, expertise with technology, and sufficient facilities for students.